Implementation of a curriculum with a humanistic perspective: teacher perceptions (Praxis Educativa, 2025)
The perceptions of elementary school teachers about the curriculum with a humanistic perspective and the type of practices they associate with it were analyzed. It is based on the interpretative paradigm, phenomenological design, by means of a questionnaire and in-depth interviews. Eighty-seven teachers participated in the questionnaire and 20 in the interviews from the northern and southeastern regions of Chihuahua, Mexico. The results indicate that teachers recognize the importance of humanism in education and associate it with practices that consider the recognition of their students as unique persons, with particular realities; teaching beyond the cognitive that seeks socioemotional wellbeing; planetary awareness that transcends from the ecological to the reflection on social problems; respect for diversity, through collaborative work and from a Human Rights perspective. It is suggested to take this study to other contexts to have a broader view of this phenomenon present in the world.
Keywords: humanism; primary school teachers; teaching practice; education; primary school; students